2002
DOI: 10.2172/793407
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Atmospheric Copper Sulfidation and Evaluation of Parallel Experimentation Techniques

Abstract: A physics-based understanding of material aging mechanisms helps to increase reliability when predicting the lifetime of mechanical and electrical components. This report examines in detail the mechanisms of atmospheric copper sulfidation and evaluates new methods of parallel experimentation for high-throughput corrosion analysis. Often our knowledge of aging mechanisms is limited because coupled chemical reactions and physical processes are involved that depend on complex interactions with the environment and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 21 publications
2
16
0
Order By: Relevance
“…Rutherford Backscattering (RBS) experiments have verified the mechanism for growth of the copper sulfide film [11]. It was shown that the copper sulfide film grows at the sulfide-water film interface and not at the buried sulfide-copper interface.…”
Section: E-mentioning
confidence: 95%
See 3 more Smart Citations
“…Rutherford Backscattering (RBS) experiments have verified the mechanism for growth of the copper sulfide film [11]. It was shown that the copper sulfide film grows at the sulfide-water film interface and not at the buried sulfide-copper interface.…”
Section: E-mentioning
confidence: 95%
“…During this stage, sulfide growth is controlled primarily by either gas phase mass transport or by partial surface reaction control [6]. Detailed experiments by Braithwaite et al [11] have shown that the growth rate in this stage is roughly independent of the relative humidity level. This experimental observation is in stark contrast with many other atmospheric corrosion systems where the corrosion rate is typically negligible until a critical relative humidity is reached, at which point sufficient water is present on the surface to support electrochemical reactions.…”
Section: Bare Coupon H 2 S Experiments With Modeling Attemptsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 To formulate the constitutive equations needed to describe these effects and the physicochemical processes ongoing during the sulfidation of an electrical contact, two levels of experimental studies were performed. In the first series, the sulfidation kinetics of bare copper were characterized.…”
Section: Constitutive Equationsmentioning
confidence: 99%